Dinasti Politik pada Pemilihan Bupati Kabupaten Batanghari 2020: Analisis Perilaku Pemilih - Muhammad, Hatta Abdi; Anggara, Dony (Faculty of SociaI and Political Sciences (FISIP), Universitas Islam Negeri (UIN) Bandung, 2021)
The phenomenon of political dynasty is one of important topics in political studies in Indonesia. This article examines how political elite attempt to preserve their power with a special reference to the case of Batang Hari regency in Jambi province, Indonesia. Using descriptive qualitative method, this article shows that political dynasty is made possible due to economic factors as well as traditional charteristics of voters. Accute social and economic condition facing communities such as low income and education contributed to the the rise and preservation of elite’s political dynasty. All this has resulted in the pragmatic and instant attitude within communities and the irrationality of voters’ behavior that in turn provided elite with opportunities to maintain their political dynasty.